2019
DOI: 10.1074/jbc.ra118.007201
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte-specific deletion of lysosomal acid lipase leads to cholesteryl ester but not triglyceride or retinyl ester accumulation

Abstract: Lysosomal acid lipase (LAL) hydrolyzes cholesteryl ester (CE) and retinyl ester (RE) and triglyceride (TG). Mice globally lacking LAL accumulate CE most prominently in the liver. The severity of the CE accumulation phenotype progresses with age and is accompanied by hepatomegaly and hepatic cholesterol crystal deposition. In contrast, hepatic TG accumulation is much less pronounced in these mice, and hepatic RE levels are even decreased. To dissect the functional role of LAL for neutral lipid ester mobilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Conversely, cells can also internalize extracellular LAL. Enzyme exchange among different cell types and tissues explains the relatively mild phenotype of hepatocyte-specific LAL-KO mice 181 and represents a potential treatment for people with Wolman's disease by enzyme replacement therapy 182 (see below).…”
Section: Canonical Enzymology Of Acid Lipolysismentioning
confidence: 99%
“…Conversely, cells can also internalize extracellular LAL. Enzyme exchange among different cell types and tissues explains the relatively mild phenotype of hepatocyte-specific LAL-KO mice 181 and represents a potential treatment for people with Wolman's disease by enzyme replacement therapy 182 (see below).…”
Section: Canonical Enzymology Of Acid Lipolysismentioning
confidence: 99%
“…Use of a liver-specific promoter to restrict transgene expression to hepatocytes has been shown to induce antigen-specific tolerance, thereby enhancing the safety profile. 36 While liver transplantation studies in patients with LAL-D showed some clinical efficacy, suggesting that liver is the primary organ in need of treatment, liver-specific deletion of LIPA in mice fails to manifest many aspects of LAL-D, 37 which suggests that constitutive organ expression may be needed for maximal therapeutic benefit. While we did observe increased LAL enzyme activity in the liver at P60 and P120, this did not completely correct disease phenotypes in Lipa −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of liver-specific Lipa deficiency, hepatic TG and RA remain unaltered in normal chow. However, an approximately 30% reduction of triglycerides in the liver in the liver-specific Lipa -cKO mice with a high-fat diet containing vitamin A at the age of five months [ 64 ]. These results clearly demonstrated that hepatic LAL plays a key role in CE metabolism in the liver, while hydrolysis of triglyceride and retinoic acid is mediated by uncharacterized lipase.…”
Section: Phenotype Of Lipa -Deficient Micementioning
confidence: 99%